Perbedaan Sakramen dalam Agama Kristen Katolik dan Kristen Protestan - Nur Maria Setyorini; M. Qomarul Huda; Mohammad Arif; M. Thoriqul Huda (Gunung Djati Conference Series, 2023)
This study aims to discuss the differences in the sacraments in Catholic Christianity and Protestant Christianity. This study uses a qualitative approach with the method of library research (library research). The objects studied in this study are the sacraments in Catholic Christianity and Protestant Christianity. The results of the research and discussion show that the differences in the sacraments in the two religions lie in the sacraments of confirmation, reconciliation, holy oil, priesthood and marriage. And both have similarities in the sacrament of baptism and the sacrament of the Eucharist (God's Supper). This study concludes that each religion, both Catholic and Protestant, has the same religious doctrine, but differs in its sacred ceremonies (sacraments).